PENGARUH KINERJA KARYAWAN TERHADAP KEPUASAN NASABAH (Studi Kasus di BPRS Amanah Ummah Leuwiliang) - Maulana, Irham (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
BPRS Amanah Ummah Leuwiliang, which is a business entity engaged in the service sector, must pay attention to the performance of its employees in providing services to customers. Because the services provided by these employees will have an impact on the company, both positive and negative. From this, problems arise that make the author interested in conducting research to show that there is a positive effect of employee performance on customer satisfaction at BPRS Amanah Ummah Leuwiliang. This study uses quantitative research methods, namely by distributing questionnaires to 100 respondents as a sample to obtain responses about the dimensions of employee performance on customer satisfaction. In addition to using a questionnaire, the writer also uses interview, observation and documentation methods. The number of samples was determined by simple random sampling technique. As for statistical testing with simple linear regression test, hypothesis testing with t test, and R2 test (coefficient of determination). The results of hypothesis testing with t test on variable X (employee performance) obtained a value of t count 10.587 > t table 1.984, so employee performance has a positive and significant effect on customer satisfaction at BPRS Amanah Ummah Leuwiliang. While the coefficient of determination test results show that employee performance affects customer satisfaction by 53.4% and the remaining 46.6% is influenced by other factors not included in this study.